THE EFFECT OF HYDROTHERMAL PRETREATMENT AND SOLID-STATE FERMENTATION USING TRICHODERMA VIRIDE ON LIGNOCELLULOSE DEGRADATION AND HUMIC ACID SYNTHESIS FROM CORN COB WASTE (ZEA MAYS L.) - Nathania Gunawan, Klara
Corn is one of the staple food commodities in Indonesia, with production reaching 22.5 million tons per year. However, corn cobs are often discarded as waste with an estimated annual amount of around 5.7 million tons and this is expected to increase. Corn cobs contain a significant amount of lignocellulosic components, consisting of approximately 20-30% cellulose, 35-40% hemicellulose, and 15-20% lignin. The lignocellulosic components can be degraded through fermentation using the biological agent like Trichoderma viride and used in the formation of humic acid. An initial treatment of hydrothermal is carried out to break down part of the lignocellulose structure and enlarge the biomass's pores. This study aimed to determine the effect of solid substrate fermentation time by Trichoderma viride on the lignocellulosic content of corn cobs and the yield of humic acid, with variations in initial hydrothermal treatment times of 30, 45, and 60 minutes. Fermentation was conducted for 35 days in a closed and dark room with variations in time intervals of 7, 14, 21, 28, and 35 days. The lignocellulosic content decreased during the 35- day fermentation period with variations in initial hydrothermal treatment times, with the lowest content found at the 60-minute initial hydrothermal treatment time. The humic acid content of corn cobs increased during the 35-day fermentation period with variations in initial hydrothermal treatment times. The highest humic acid content was obtained on the 35th day of fermentation with a 60-minute initial hydrothermal treatment time, reaching 6.5%. Correlation analysis results indicated that cellulose degradation significantly influenced humic acid formation, while hemicellulose and lignin degradation had the opposite effect.